3D printing of musculoskeletal tissues: impact on safety and health at work. Issue 16 (18th August 2019) - Petretta, Mauro; Desando, Giovanna; Grigolo, Brunella; Roseti, Livia
ABSTRACT: Additive manufacturing (commonly referred to as 3D printing) created an attractive approach for regenerative medicine research in musculoskeletal tissue engineering. Given the high number of fabrication technologies available, characterized by different working and physical principles, there are several related risks that need to be managed to protect operators. Recently, an increasing number of studies demonstrated that several types of 3D printers are emitters of ultrafine particles and volatile organic compounds whose harmful effects through inhalation, ingestion and skin uptake are known. Confirmation of danger of these products is not yet final, but this provides a basis to adopt preventive measures in agreement with the precautionary principle. The purpose of this investigation was to provide a useful tool to the researcher for managing the risks related to the use of different kinds of three-dimensional printers (3D printers) in the lab, especiallyconcerning orthopedic applications, and to define appropriate control measures. Particular attention was given to new emerging risks and to developing response strategies for a comprehensive coverage of the health and safety of operators.